Keberhasilan Anak Perempuan Fatherless: Tinjauan Core Self Evaluation (CSE) Positif di Panti Asuhan Intifa Ikhwaniyah Condet Jakarta Timur - Febriani, Cindini; Fitriyani, Hilma; Badrujaman, Aip (Universitas Muhammadiyah Metro, 2025)
This study aims to explore the success of fatherless girls in the context of a positive Core Self Evaluation (CSE) review at the Intifa Ikhwaniyah Orphanage, Condet, East Jakarta. A qualitative approach through case studies was used in this study, with data collection techniques through indepth interviews, participant observation and documentation studies. The results of the study indicate that the success of fatherless girls in the Intifa Ikhwaniyah Orphanage who have positive CSE can be influenced by various factors. Internal and external factors such as economic conditions, social class, the role of orphanage care, orphanage programs and services, social interaction with the environment, peer support, belief in the belief that suffering is a motivation for survival, and self-perception, play an important role in shaping positive CSE in fatherless girls. The implications of this study indicate the need for greater attention to the development of positive CSE in fatherless girls in orphanages.